2014
DOI: 10.12669/pjms.311.4104
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume can Predict Cerebrovascular Events in Patients with Sickle Cell Anemia

Abstract: Objective:The purpose of this study was to determine the impact of mean platelet volume (MPV) on the frequency and severity of vaso-occlusive and cerebrovascular events in patients with sickle cell anemia (SCA).Methods: The 238 cases diagnosed with SCA were evaluated retrospectively with respect to the occurrence of painful crisis for the previous year. The incidence, severity and type of the vaso-occlusive crises of the patients with SCA between March 2010 and March 2011 were recorded. The last MPV values in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Platelets may also promote endothelial activation and erythrocyte adhesion by stimulating several major endothelial adhesion molecules, including vascular adhesion molecule (VCAM-1) (133) and by forming an increased number of platelet-erythrocyte (134, 135), platelet-monocyte (136) and platelet-neutrophil aggregates (136). Although the underlying mechanisms are unclear, there is cross-sectional evidence that patients with SCI or overt ischemic stroke have higher mean platelet values than patients without lesions on MRI (137). Also, thrombocytosis (platelets > 500 * 10 9 /L) is associated with cognitive impairment across multiple domains in children with SCD (138), and elevated levels of erythrocyte and platelet derived microparticles have been described in those with a history of overt stroke (139).…”
Section: Hypercoagulability and Embolic Eventsmentioning
confidence: 99%
“…Platelets may also promote endothelial activation and erythrocyte adhesion by stimulating several major endothelial adhesion molecules, including vascular adhesion molecule (VCAM-1) (133) and by forming an increased number of platelet-erythrocyte (134, 135), platelet-monocyte (136) and platelet-neutrophil aggregates (136). Although the underlying mechanisms are unclear, there is cross-sectional evidence that patients with SCI or overt ischemic stroke have higher mean platelet values than patients without lesions on MRI (137). Also, thrombocytosis (platelets > 500 * 10 9 /L) is associated with cognitive impairment across multiple domains in children with SCD (138), and elevated levels of erythrocyte and platelet derived microparticles have been described in those with a history of overt stroke (139).…”
Section: Hypercoagulability and Embolic Eventsmentioning
confidence: 99%
“…This inverse relationship was found in all geographic regions of the DOVE study, and has been documented in healthy populations [17] Segal and Moliterno [18] found that subjects of African descent had higher platelet counts than other ethnic groups that were not the result of environmental factors and were possibly genetic and/or hormonally driven. Celik et al [19] reported that platelet volume was higher in subjects with cerebrovascular events and increased with incidence of VOCs, suggesting that higher mean platelet volumes may be an early predictor of future cerebrovascular events. Although additional research would be required, it is interesting to note that subjects from SSA, who had the lowest mean platelet volume at baseline, also had low VOC rates during the study.…”
Section: Discussionmentioning
confidence: 99%
“…Acipayam et al [12] Adekile et al [13] Akar and Adekile [14] Al-Ghazaly et al [15] Al-Saqladi et al [16] Hanafy et al [17] Inati et al [18] Alsultan et al [19] Alsultan et al [20] Alsultan et al [21] Alsultan et al [22] Al-Saqladi et al [23] Celik et al [24] Rafique et al [25] Haq et al [26] Inati et al [27] Helvaci et al [28] Nimgaonkar et al [29] Jain et al [30] Overall Heterogeneity: τ 2 = 0.00, I 2 = 79.67%, H 2 = 4.92 3.6. Publication Bias.…”
Section: Gujjar Et Al [11]mentioning
confidence: 99%